Fatores que influenciam a adesão do mobile banking por idosos - Depiné, Fábio Marcelo (2021)
This work aims to understand the relationship of the elderly with mobile banking, seeking to perceive if the service is being used by the elderly population, if there are divergences in use between an inner city and a metropolis, and to investigate the factors that influence its acceptance or rejection, in order to contribute to the improvement of the service and benefit both the banks, but especially the elderly, as a way to support active aging. To elucidate this issue, this research is based on the extension of the Unified Theory of Acceptance and Use of Technology (UTAUT2), also adding the constructs trust, perceived security and privacy, and the education and salary moderators, in a comparative between the contexts of small country town and a big urban center. 13 hypotheses were tested in an applied, descriptive and explanatory research, with a quantitative method. Data collection took place through a questionnaire, with 49 Likert-type questions of 7 points and another 16 general questions, applied to a sample of 101 elderly people in Taió/SC and 220 in Brasília/DF. Descriptive analysis was performed for general questions and, for Likert scale questions, partial least squares structural equation modeling (PLS-SEM) as well as multiple group analysis (PLS-MGA) were used. The results indicate that the elderly are using mobile banking, that there are reasonable divergences in use between the countryside and the metropolis, and point out the factors that influence its adoption.